2019
DOI: 10.1055/s-0039-1678539
|View full text |Cite
|
Sign up to set email alerts
|

Necessary Factors to Achieve Deep Flexion for Asian Populations after Oxford Unicompartmental Knee Arthroplasty

Abstract: There have been many reports on the clinical outcomes of Oxford unicompartmental knee arthroplasty (UKA); however, none have investigated the influence of flexion angle after UKA on clinical outcomes. The objective of this study was to clarify the relationship between outcomes and the postoperative maximum flexion angle and reveal the necessary factors for maximum flexion angle ≥ 140 degrees which is considered necessary for Asian populations. We categorized 212 UKA patients into the following three groups bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 41 publications
0
8
1
Order By: Relevance
“…The anterior tibial cortex was tilted about 3° from this axis, 31 so taking this into account, the osteotomy was almost on target in all knees. Although the posterior tibial slope is reportedly an important factor that relates to the clinical outcomes, such as the angle of flexion postoperatively and rate of survival in patients undergoing UKA, 32,33 it did not relate to the KCDs in this study.…”
Section: Discussioncontrasting
confidence: 57%
“…The anterior tibial cortex was tilted about 3° from this axis, 31 so taking this into account, the osteotomy was almost on target in all knees. Although the posterior tibial slope is reportedly an important factor that relates to the clinical outcomes, such as the angle of flexion postoperatively and rate of survival in patients undergoing UKA, 32,33 it did not relate to the KCDs in this study.…”
Section: Discussioncontrasting
confidence: 57%
“…A recent study on the Japanese population with an average of approximately 3-year follow-up in single surgeon series of Oxford UKA demonstrated that postoperative knee flexion !140 degrees was associated with tibial component posterior slope. 20 In the current study, regardless of surgeons, it was observed that larger knee flexion following UKA was associated with !80 KOOS subscale of symptoms at both 1 and 2 years postoperatively. For the Asian population that needs deep knee flexion in their daily living activities, especially in their sitting positions, 36,37 it has been estimated that the knee's postoperative ROM-especially knee flexion angleshas a significant positive effect on PRO.…”
Section: Discussionmentioning
confidence: 52%
“…[17][18][19] Additionally, some retrospective clinical studies have shown that the coronal or sagittal alignment of the tibial component was linked to clinical results, such as the implant survival rate [14][15][16] or the postoperative knee flexion angles. 20 However, to date, there is limited data available on the implant alignment's direct influence on the clinical score,…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous previous studies have considered KOOS scores of 90 or more after knee joint arthroplasty as excellent results. 9,21 As a consequence, the patients enrolled in this study were divided into two groups based on their 1-year postoperative KOOS scores of each subscale. The groups were as follows: group H (each subscale) consisted of patients with !90 scores and group L (each subscale) consisted of patients with <90 scores.…”
Section: Statistical Analysesmentioning
confidence: 99%